Vibrational Spectra of the OH Radical in Water: Ab Initio Molecular Dynamics Simulations and Quantum Chemical Calculations Using Hybrid Functionals. Issue 12 (5th November 2020) - Apostolidou, Christina
Abstract: The OH radical has remarkable features in aqueous environments. Studies of vibrational properties can uncover more information about this omnipresent radical. However, infrared spectra of the OH radical in water represent a challenging task. This work studies the OH ⋆ stretching vibration from the gas phase for OH ⋆ ‐wn (w = water, n = 0–5) clusters to the bulk phase for OH ⋆ ‐w31 via ab initio molecular dynamics (AIMD) simulations with B3LYP‐D3 and the maximally localized Wannier function scheme. The infrared spectrum of pure liquid water reveals from an AIMD simulation with 32 water molecules a characteristic bulk phase. The OH ⋆ stretching vibration is continuously red‐shifted from the gas phase to liquid water. This fact is supported by static DFT and RI‐MP2 calculations. A comparison of Wannier and radical Voronoi tessellation spectra leads to the same result for all clusters, which implies the absence of delocalized electrons. Despite the use of van der Waals radii, the Voronoi approach is able to distinguish between strong and weak hydrogen bonds, emphasizing the flexibility of this approach toward different hydrogen bond types. The stretching vibration of the OH ⋆ in the gas phase appears as a doublet due to the coupling of rotation and stretching. Abstract : Ab initio molecular dynamics simulations are performed to study the OH stretching vibration trend from the gas phase up to liquid water. A continuous decreasing red‐shift is shown. Wannier and Voronoi approaches reveal the absence of delocalized electrons. The partitioning via van der Waals radii in the Voronoi approach, has the flexibilty to distinguish strong and weak hydrogen bonds.